Tail suspension test to evaluate the antidepressant activity of experimental drugs - Muhammad Aslam (Bangladesh Pharmacological Society, 2016)
Tail suspension test (TST) is a common behavioral paradigm used to evaluate the antidepressant activity of experimental drugs. Like the forced swimming test, in this test the animals are set in an inescapable yet modestly distressing circumstance. In the tail suspension test, the extent of immobility is thought to be associated with the depressive-like condition of the animal and is significantly diminished by antidepressant drugs. Video clips of Methodology: Pre-experiment: 53 sec   Full Screen   Alternate Experiment: 7 min 31 sec   Full Screen   Alternate